Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12471-016-0943-2
|View full text |Cite
|
Sign up to set email alerts
|

Life-long tailoring of management for patients with hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common genetic heart disease, characterised by complex pathophysiology and extensive genetic and clinical heterogeneity. In most patients, HCM is caused by mutations in cardiac sarcomere protein genes and inherited as an autosomal dominant trait. The clinical phenotype ranges from severe presentations at a young age to lack of left ventricular hypertrophy in genotype-positive individuals. No preventative treatment is available as the sequence and causality of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
(50 reference statements)
1
19
0
Order By: Relevance
“…Stage IV patients show less hypertrophy of the IVS and increased dimensions of both LV and left atrium. [8] Both our patient groups showed a predominance of the male sex (stage II: 56% and stage IV: 60%) which is in line with earlier research (ranging from 55-72% in end-stage HCM). [25][26][27][28][29][30] As for stage II HCM patients, based on our recent study, we have proposed that women may be diagnosed too late because the cut-off value for IVS is not corrected by body surface area.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Stage IV patients show less hypertrophy of the IVS and increased dimensions of both LV and left atrium. [8] Both our patient groups showed a predominance of the male sex (stage II: 56% and stage IV: 60%) which is in line with earlier research (ranging from 55-72% in end-stage HCM). [25][26][27][28][29][30] As for stage II HCM patients, based on our recent study, we have proposed that women may be diagnosed too late because the cut-off value for IVS is not corrected by body surface area.…”
Section: Plos Onesupporting
confidence: 92%
“…[6] To classify the different forms of HCM, Olivotto et al [7] described different stages in cardiac disease progression ranging from unaffected mutation carriers to end-stage failing HCM patients. [8] The majority of HCM patients develop a 'classic' (stage II) form of HCM with the characteristic septal thickening, LV outflow tract obstruction (LVOTO) and diastolic dysfunction. Approximately 5-10% of all HCM patients progress to the severe end-stage of HCM (stage IV), which is characterized by thinning of the IVS and LV wall, and left atrial dilation, extensive fibrosis and impaired systolic function.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical expression can be extremely diverse, ranging from symptomatic patients with severe hypertrophic remodeling accompanied by cellular disarray, fibrosis, and microvascular dysfunction, to asymptomatic mutation carriers with a structurally normal heart. Most patients display the classic form of HCM with asymmetric septal hypertrophy and left ventricle outflow tract obstruction at rest or during exercise . A small number of HCM individuals (~ 4%) progress to end‐stage HCM, defined by systolic dysfunction (ejection fraction <50%) and regression of hypertrophy and/or cavity dilation .…”
mentioning
confidence: 99%
“…Hypertrophy may initially be adaptive and help preserve systolic function, but sustained pathological hypertrophy will lead to a decompensated phase with deleterious consequences [1,2] . Epidemiological studies have revealed that cardiac hypertrophy is an independent risk factor for cardiac dysfunction and sudden death [3][4][5] . However, despite the great strides that have been made over the past decades in elucidating the pathogenesis of cardiac hypertrophy, the signaling pathways associated with this complex clinical syndrome are far from fully understood.…”
Section: Introductionmentioning
confidence: 99%